2021
DOI: 10.1002/cpa.22014
|View full text |Cite
|
Sign up to set email alerts
|

Arnold Diffusion, Quantitative Estimates, and Stochastic Behavior in the Three‐Body Problem

Abstract: We consider a class of autonomous Hamiltonian systems subject to small, time‐periodic perturbations. When the perturbation parameter is set to zero, the energy of the system is preserved. This is no longer the case when the perturbation parameter is non‐zero. We describe a topological method to establish orbits which diffuse in energy for every suitably small perturbation parameter ε>0. The method yields quantitative estimates: (i)the existence of orbits along which the energy drifts by an amount independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 90 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…From (74), (75), ( 76) and (78) we obtain (7). Similarly, from (73), ( 75), ( 76) and (77) we have (8). We have thus shown that Γ is a well defined homoclinic channel.…”
Section: Appendix a Proof Of Lemma 27mentioning
confidence: 58%
See 4 more Smart Citations
“…From (74), (75), ( 76) and (78) we obtain (7). Similarly, from (73), ( 75), ( 76) and (77) we have (8). We have thus shown that Γ is a well defined homoclinic channel.…”
Section: Appendix a Proof Of Lemma 27mentioning
confidence: 58%
“…The shadowing of orbits is then automatically taken care of by [4], and we do not need to carry out the explicit construction of windows as in [8]. Our results are weaker though than [8].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations